Odpowiedzi

2010-03-05T16:42:17+01:00
A)(-24 7/4)+14 2/11= (-103/4) + 156/11= (-1133/44) + 624/44 = (-509/44) = (- 11 25/44)
b)(-3 2/3)-4 = (-11/3) - 4 = (-11/3) - 12/3 = (-23/3) = (-7 2/3)
c)-6,3-2,2 = (-63/10) - 22/10 = (-85/10) = (-8,5)
d)2,6+(-10) =2,6 - 10 = 7,4
e)-0,2-(-0,7) =(- 0,2) + 0,7 = 0,5

zad.Rozwiąż równanie.
a)2(x+3)=10
2x+6=10
2x=10-6
2x=4 |:2
x=2
b)3(x-1)+2=8
3x-3+2=8
3x=8+3-2
3x=9 |:3
x=3
c)2(13-x)-9=-7
26-2x-9=-7
-2x=-7-26+9
-2x=-24 | :(-2)
x=12
d)3(1-x)+2=-7
3-3x+2=-7
-3x=-7-3-2
-3x=-12 | :(-3)
x=4
e)3(x+3)=2(x+4)+x+1
3x+9=2+8+x+1
3x-x=11-9
2x=2 |:2
x=1